Writing truth as non-violence : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Webb, Simon Christopher (Massey University, 2011)
This thesis explores some of the ways violence can constrain, inform, and otherwise impact upon psychological theory, the ways psychological theory can contribute to various forms of violence, and some of the implications of this reflexive cycle. Arguing for non-violence as a truth criterion of psychological knowledge claims, the thesis sets out to question the conditions of possibility for producing non-violent psychological theory. Drawing upon contemporary theories of language, subjectivity, and power, it discusses technologies of truth production in terms of violence. The work of literary theorist and feminist post-structuralist philosopher Judith Butler is discussed in this context. After developing a set of theoretical resources for addressing reflexive epistemological problems of violence, some practice implications of non-violent psychological theory are considered in relation to the specific domain of forensic psychology. Returning to discussion of the broader theoretical issues, the thesis identifies some promising areas of focus for non-violent theory development. A key claim arising from this discussion is that the tradition of validity as representational accuracy or referential truth is closely linked to the prioritisation of power in many Western scientific, economic and other cultural enterprises. In this context psychology can emulate other sciences and produce technologies for more efficient control of subjectivity; but it can also use these technologies reflexively to address the desires embodied in its own pursuit of theoretical power, actively challenging the truth status of violent knowledge claims. The initial commitment to non-violent truth is now articulated as an argument that a commitment to forms of encounter with others that do not objectify those others involves a theoretical commitment to validating knowledge claims in terms of social justice. This calls into question the traditional hierarchy of “hard” and “soft” sciences, in which the truth claims of psychology and other social sciences are positioned as having to conform to the truth claims of natural sciences like physics and chemistry: a social epistemological framework positions psychological theory as a key resource for assessing the truth status of knowledge claims in other sciences. The thesis raises questions around this opportunity, both with respect to some of the details of its possible theoretical forms, and its possible political implications in academic, therapeutic and other contexts.
Keywords: Violence; Non-violence; Psychology; Psychological aspects; Judith Butler; Non-violent theory development; Forensic psychology; Psychological theory